IMPLEMENTASI FLIPPED LEARNING PADA MATA KULIAH PENGANTAR TEOLOGI KRISTIANI BERBASIS PEDAGOGI IGNASIAN - Dessindi, Kristhalia (Spiritualitas Ignasian: Jurnal Kerohanian dalam Dunia Pendidikan, 2024)
This research aims to analyze the development of a flipped learning model in the course of Introduction to Christian Theology using a Communicative Theology approach based on Ignatian Pedagogy to respond to the challenges of the world of education in the current digital era. The approach chosen in the learning process is one aspect that influences student learning motivation. One learning approach appropriate to the current context is Flipped Learning, a form of blended learning that integrates technology in learning designed before the learning process, during and after class. Flipped Learning provides students with opportunities both in and outside class and even focuses on in-depth learning activities. The method used in this research is an experimental one-group pretest and posttest control design. Learning motivation aspects are assessed using pretest and posttest scores, questionnaires, and observations. The research results show that Flipped Learning increases students' learning motivation, provides space for broad and in-depth discussions in class, and encourages students to interact widely with lecturers and other students.